Climate change impacts on rice-based livelihood vulnerability in the lower Vietnamese Mekong Delta: empirical evidence from Can Tho City and Tra Vinh Province - Tran, Dung Duc (2023)
This paper assesses the livelihood vulnerability and adaptive capacity of rice-based farmers in the lower Vietnamese Mekong Delta (VMD) under the impact of climate change and environmental pressures. We interviewed 600 rice farmers in 19 communes spanning six districts of Can Tho City (middle delta) and Tra Vinh Province (coastal delta). For our analyses, we employed the Livelihood Vulnerability Index (LVI) framework and the LVI approach of the Intergovernmental Panel on Climate Change (LVI–IPCC). Results indicate that both study areas are vulnerable to climate change and environmental pressures, but the potential threat is greater in the coastal province. Farmers there have responded to climate change and environmental pressures by increasing production inputs, scaling up production areas and transforming cropping patterns, though with little investment in new equipment. Yet, their livelihoods from rice cultivation, and agricultural production in general, remain unsustainable under climate change, which is a matter of concern. This study provides empirical evidence of the vulnerability factors that most undermine farmers’ adaptive capacity and livelihood sustainability in the study areas. This will help local authorities in providing timely support to agricultural production management.